IMPLEMENTASI TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN (TJSLP), SEBAGAI KOMPLEMENTARI DANA PEMBANGUNAN DI JAWA TENGAH - Rudjito, Hermawan (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
Corporate Social Responsibility (CSR/ TJSLP) is not entirely new, Central Java Province only on January 26 2017 with the enactment of Regional Regulation No. 2 of 2017 concerning Corporate Social Responsibility (CSR/ TJSLP) stretches to optimize this potential. The Covid-19 pandemic that hit Indonesia in early 2020, also triggered the Central Java Provincial Government in particular to start introducing alternative sources of financing. Writing this material aims to contribute positively to provide enlightenment and alternative sources of financing through more optimal management of CSR funds. The method used in writing this material is a qualitative analysis method, with data sourced from the Central Java Province TJSLP Forum and other accurate sources. The literature review referred to in writing is a traditional review with the paper used as a reference still on the same topic of discussion as the research being carried out regarding the implementation and implications of the allocation and implementation of the TJSLP/ CSR program. The results of the study have shown that the use of TJSLP funds in Central Java Province has officially accommodated starting from the annual planning document since 2020, and will consistently be implemented in subsequent years by further improving the planning and allocation mechanisms. The conclusion of this study is that the management of TJSLP/CSR allocation funds in its implementation provides an alternative for development financing in Central Java.